Prevalence and risk indicators of tooth wear in 17 year old school children in Colombo District in Sri Lanka. - Ratnayake, N.C (My University, 2011)
Tooth wear has been recognized as an emerging dental problem among adolescents in the developed countries. Many authors attributed this disease trend to the increased consumption countries. Many authors attributed this disease trend to the increased consumption of aciodic food, mainly carbonated beverages, associated with improving socio-economic standards. However, there is paucity of information on tooth wear among adolescents from developing countries. The study consisted of two components. A crosssectional school based study was conducted in order to determine prevalence, severity, distribution and risk indicators of and awareness about tooth wear among the adolescents. A total of 1200 17 year olds were selected from the schools in the Colombo district using a two stage cluster sampling methods combined with probability proportional to size (PPS) technique. Subjects were requested to complete a self-administered questionnaire on potential risk indicators and knowledge about tooth wear. Prevalence of tooth wear was 22 percent, 14 percent only had tooth wear lesions confined to the enamel while 9 percent had tooth wear lesions extending up to the dentine

Tooth wear has been recognized as an emerging dental problem among adolescents in the developed countries. Many authors attributed this disease trend to the increased consumption countries. Many authors attributed this disease trend to the increased consumption of aciodic food, mainly carbonated beverages, associated with improving socio-economic standards. However, there is paucity of information on tooth wear among adolescents from developing countries. The study consisted of two components. A crosssectional school based study was conducted in order to determine prevalence, severity, distribution and risk indicators of and awareness about tooth wear among the adolescents. A total of 1200 17 year olds were selected from the schools in the Colombo district using a two stage cluster sampling methods combined with probability proportional to size (PPS) technique. Subjects were requested to complete a self-administered questionnaire on potential risk indicators and knowledge about tooth wear. Prevalence of tooth wear was 22 percent, 14 percent only had tooth wear lesions confined to the enamel while 9 percent had tooth wear lesions extending up to the dentine